The effect Culture Dimensions on Quality of Integrated Reporting from the perspective of stakeholders - Gatea Al-Jubouri, Ali Khalaf; Jarad, Haider Ali (Technium Sustainability, 2021)
The preparation of integrated Reporting is a new form of reports that aims to provide a comprehensive picture of the performance of the economic unit, and because the quality of reporting is a critical aspect of integrated reports, so the research aims to demonstrate the impact of cultural dimensions on the quality of integrated reports from the point of view of stakeholders, assuming that the dimensions Cultural has a significant relationship with the extent to which the quality of integrated reporting is achieved, that the most important findings of the research states that cultural dimensions have a role in enhancing the quality of integrated reporting, that cultural dimensions have very important effects on ethics, social responsibility of economic units, organizational culture and administrative practices, The research recommends, in light of the different cultural dimensions between different business environments, whether national or international, the need to interact with the environment and the societies in which the economic unit operates, to enable it to provide environmental, social or ethical information, along with financial, strategic and governance information in an annual report.